ANALISIS IMPLEMENTASI SIKLUS PPEPP DALAM PENJAMINAN MUTU PENDIDIKAN TINGGI DI INDONESIA - Mulyani, Sri; Sohiron, Sohiron (Jurnal Manajemen Pendidikan, 2026)
Quality assurance in higher education in Indonesia requires the implementation of a structured and sustainable system to ensure the achievement of institutional performance and compliance with accreditation requirements. This article aims to examine the implementation of the PPEPP cycle (Establishment, Implementation, Evaluation, Control, and Improvement) within the higher education quality assurance system, highlighting the role of each stage as an integrated and continuous quality improvement cycle. This study adopts a qualitative descriptive–analytical approach through a review of policy documents, regulations, and relevant academic literature related to quality assurance and higher education accreditation. The results indicate that the establishment of contextual and relevant standards constitutes the primary foundation for the effective implementation of the PPEPP cycle. Consistent implementation of these standards strengthens the effectiveness of the internal quality assurance system. Furthermore, evaluation and control conducted through internal quality audits serve as reflective mechanisms to ensure performance accountability, while continuous quality improvement directly supports the achievement of outcome-based accreditation. These findings demonstrate that the PPEPP cycle functions not merely as an administrative requirement, but as a strategic framework for enhancing the quality and competitiveness of higher education institutions in a sustainable manner.